Tissue concentration of vascular endothelial growth factor is not related to the depth of trophoblastic invasion in ampullary pregnancies—A pilot study - Teshima, Décio Roberto Kamio; Pereira, Pedro Paulo; Francisco, Rossana Pulcineli Vieira; De Oliveira, Matheus Abelo; Schulz, Regina; Antonângelo, Leila; Cabar, Fábio Roberto (Frontiers in Pharmacology, 2022)
Introduction: The factors that modulate trophoblastic invasion into the tubal wall remain uncertain. Moreover, it is known that the concentration of vascular endothelial growth factor (VEGF) is increased in cases of deeper trophoblastic invasion in the fallopian tubes. Objective: This study aimed to assess if there is a correlation between VEGF tissue expression and the depth of trophoblastic infiltration into the tubal wall in patients with ampullary pregnancy. Methods: A cross-sectional study was conducted in patients with a diagnosis of tubal pregnancy in the ampullary region who underwent salpingectomy. Inclusion criteria were spontaneously conceived singleton pregnancies, diagnosis of tubal pregnancy in the ampullary region, and radical surgical treatment. A lack of agreement regarding the location of the tubal pregnancy and impossibility of either anatomopathological or tissue VEGF analysis were the exclusion criteria. Histologically, trophoblastic invasion into the tubal wall was classified as grade I when limited to the tubal mucosa, grade II when it reached the muscle layer, and grade III when it comprised the full thickness of the tubal wall. A total of 42 patients fulfilled the inclusion criteria and were selected to participate in the study. Eight patients were excluded. After surgery, tissue VEGF expression was measured by immunohistochemistry and the point counting technique. Results: Histological analysis revealed that eight patients had stage I tubal infiltration, seven had stage II, and 19 had stage III. The difference between the percentage of VEGF expression in the trophoblastic tissue was not significant in relation to the degree of trophoblastic invasion (p = 0.621) (ANOVA). Trophoblastic tissue VEGF showed no statistical difference for prediction of both degrees of trophoblastic invasion (univariate multinomial regression). Conclusion: The depth of trophoblastic penetration into the tubal wall in ampullary pregnancies is not associated with tissue VEGF expression.